Analysis of the Factors Related to Intracranial Infection after Brain Tumor Surgery. (5th September 2022) - Chen, Weiying; Sheng, Danli
Abstract : In order to explore the factors related to intracranial infection after brain tumor surgery, a retrospective analysis is conducted in this study. According to the patients with intracranial infection after brain tumor surgery in our hospital from January 2020 to October 2020, clinical data are divided into different groups and some indicators are put into the multiple regression model for multivariate analysis. The factors related to intracranial infection after brain tumor surgery are analyzed, and the clinical effect of a detailed management plan based on the abovementioned risk factors to prevent intracranial infection in patients after brain tumor surgery is observed. Multiple regression models demonstrate that complicated underlying diseases, operation time, and intraoperative blood loss are independent risk factors for postoperative intracranial infection.